Differential diagnosisof manifestations of syphilis and aids with lichen planusin mouth: case report - Moleri, Andrea B.; Lobo, Camila B.; Santos, Felipe R; Silva, Ednaldo José da; Gouvêa, Cresus Vinícius D.; Moreira, Luiz Carlos (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Syphilis follows a semiological course in which it appears, disappears, and reappears with various signs and symptoms, demanding clinical and laboratorial knowledge that lead to its diagnosis from examiners. The dissemination of Treponema pallidum involves practically all of the organic systems, complicating diagnosis and justifying the historic consecration that syphilis is a large simulator of various other diseases. The oral mucosa is an important signalizing area for disease recognition by way of a systematic and detailed clinical examination. Unfortunately, the incidence and prevalence of syphilis in the world does not express clear signs of pronounced decrease, especially in Latin America and in the so-called emerging countries. The purpose of the present study is to report the case of a patient with clinical oral manifestations of syphilis and aids (acquired immunodeficiency syndrome) that were primarily interpreted as lichen planus.